دور المراجعة الداخلية في إدارة المخاطر في الوحدات الاقتصادية الحكومية بليبيا: دراسة ميدانية على كلية صرمان للعلوم والتقنية - ابوبكر سعيد الزنين; مفتاح خليفة الأطرش (Surman Journal of Science and Technology, 2025)
The purpose of this research is to investigate the function of internal audit in risk management through a review of the accounting literature pertinent to the topic. It relies on the analysis of a standardized questionnaire sent to all heads of internal audit along with several interviews conducted with them. The research ended with a collection of results derived from the feedback it gathered and the examination of the field data. The findings show that, from the employees' viewpoint, the internal audit function within the administrative unit being analyzed is robust, as evidenced by its overall arithmetic mean of 3.81 out of 5 on the five-point Likert scale. Moreover, the degree of risk evaluation in the examined administrative units was strong from the perspective of the employees, which was shown by its overall arithmetic average of 3.53 out of 5 on the identical scale. The influence of internal auditing on assessing the risks encountered by the relevant administrative units, as viewed by their employees, is statistically significant. This research seeks to advance upcoming studies on a significant subject like risk management.